Heptazine-Based π-Conjugated Materials for Light-Emitting - Li, Jie; Tao, Li; Wang, Yanqing; Yao, Yali; Guo, Qiang (Frontiers in Chemistry, 2021)
On the basis of planar and relatively rigid nitrogen-rich heterocyclic system of the heptazine core, heptazine-based π-conjugated materials have aroused widespread attention over the past decade by virtue of the fascinating electronic, optical, thermal, and mechanical properties in the fields of light-emitting, photocatalysis, sensors, environmental remediation, and so forth. However, there are still several obstacles to be solved before practical applications, such as low photoluminescence quantum efficiencies for light-emitting and weak visible absorption for photocatalysis. To further enhance various properties of heptazine-based π-conjugated materials, a series of strategies have been developed, including ingenious molecular design and modification, novel synthetic, and preparation methods. In this review, the significant progress of monomeric and polymeric heptazine-based π-conjugated materials and their applications typically in light-emitting are reviewed, which is beneficial for the acceleration of practical applications of heptazine-based materials and devices.